PENERAPAN KEBIJAKAN PENGGUNAAN ENERGI LISTRIK TERHADAP KINERJA USAHA MIKRO KECIL DAN MENENGAH DI PROVINSI JAWA TIMUR - Hatane Semuel (Jurnal Manajemen Pemasaran, 2014)
Micro, Small, and Medium Enterprise (SME) is one of the main forms thriving business in Indonesia. The use of electrical energy is a decisive component of cost of products. Stimulus by the government through the Indonesian Government Regulation on conservation of energy is a systematic attempt, planned and integrated in order to conserve resources and increase domestic energy utilization efficiency. Such efforts positively impact the business performance of SMEs in Java Timur. Evaluation of energy conservation policies among SMEs, is done through building the concept of government policy as a stimulus to encourage changes in the behavior of individual workers and business systems, which are plotted in organsasi work culture, and impact on organizational performance. The study of 150 SME entrepreneurs in the city of Surabaya and Sidoarjo district shows that there was a positive influence on the energy conservation policy work behavior of individuals and organizations working system, both of which impact positively on the quality of the work culture of the organization and then a positive impact on performance.